2017
DOI: 10.3390/ijerph14080900
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Fall Injury in Rural Bangladesh

Abstract: Globally, falls are the second leading cause of unintentional injury deaths, with 80% occurring in low-and middle-income countries. The overall objective of this study is to describe the burden and risk factors of falls in rural Bangladesh. In 2013, a large household survey covering a population of 1,169,593 was conducted in seven rural sub-districts of Bangladesh to assess the burden of all injuries, including falls. The recall periods for non-fatal and fatal injuries were six and 12 months, respectively. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 21 publications
3
22
2
3
Order By: Relevance
“…Our findings in preschool children are similar to observations from Bangladesh (Wadhwaniya et al 2017) and Canada (Flavin et al 2006), which showed that the Fall from a height of > 1.5 m 5 (6.0) 20 (6.8) 45 (6.1) 4 (0.9) majority of injuries in the age group 0-6 years occurred at home. In our study, the most common factor involved in mechanism of preceding activity in the preschool age group was furniture, which is in line with findings from other studies (Ali et al 2019;Pickett et al 2003;Chaudhary et al 2018;Unni et al 2012;Savitsky et al 2007;Pitone and Attia 2006).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings in preschool children are similar to observations from Bangladesh (Wadhwaniya et al 2017) and Canada (Flavin et al 2006), which showed that the Fall from a height of > 1.5 m 5 (6.0) 20 (6.8) 45 (6.1) 4 (0.9) majority of injuries in the age group 0-6 years occurred at home. In our study, the most common factor involved in mechanism of preceding activity in the preschool age group was furniture, which is in line with findings from other studies (Ali et al 2019;Pickett et al 2003;Chaudhary et al 2018;Unni et al 2012;Savitsky et al 2007;Pitone and Attia 2006).…”
Section: Discussionsupporting
confidence: 89%
“…The proportion of head injuries in the preschool age group (32%) was three times higher than that among the school age group, and the proportions of severe injuries (11%) and hospitalization (13%) were five and two times higher, respectively (Park et al 2004). These findings are supported by studies showing that head injuries are common among the youngest children (Ali et al 2019;Pickett et al 2003;Flavin et al 2006;Wadhwaniya et al 2017;Pitone and Attia 2006), which may be explained by a limited child's ability to shield the head during a fall (Park et al 2004). Based on our findings, prevention of fall injuries in preschool children should primarily address the safety of the home environment.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A study conducted on rural population in Bangladesh has reported higher odds for non-fatal falls in females compared to males. 18 Compared to men, women are more likely to trip than men in any age group, which may be related to gender differences in gait. 19 Falls were the most common mechanism of injury in our study (79.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Falls among children and adolescents in Zhuhai City were the main reason for hospitalization and outpatient/emergency department visits. A large household survey covering more than one million people in Bangladesh in 2013 found that nonfatal falls were the most common injuries [29] .…”
Section: Discussionmentioning
confidence: 99%